Post-Disaster Reconstruction of Road Infrastructure: Decision making processes in an Australian context - Gajanayake, Akvan; Khan, Tehmina; Zhang, Guomin (European Journal of Transport and Infrastructure Research, 2020)
The rehabilitation and reconstruction of damaged road infrastructure plays a vital role in the recovery of disaster affected regions. The methods and processes adopted by road-asset owners during the reconstruction phase influence the longer term effects in disaster hit communities. While the decision making processes are intended to reduce impacts, mistakes at the decision making stage can lead to an increase in social and economic impacts in the longer term. It is thus imperative to understand how decision making takes place with regard to post-disaster reconstruction of road infrastructure. The objective of this paper is to understand how road asset owners assess and prioritise post-disaster reconstruction projects in order to identify how decision making could be improved in Australia and similar regions. The results of in-depth interviews conducted with road infrastructure practitioners in disaster affected regions are presented. The findings showed that there is a gap between the research community and practitioners in the use of systematic methods to aid prioritisation and decision making. The interviews also showed that the consideration of only a limited set of engineering and financial elements can lead to unintended consequences that impede resilience. A causal loop diagram was developed to illustrate the interrelationship between factors and showed that active intervention based on a systems thinking approach will benefit post-disaster decision making. These findings suggest that the development of more localised decision making tools can increase their adoption among practitioners.